Dynamic Server Cluster Load Balancing in Virtualization Environment with OpenFlow - Wenbo Chen; Zhihao Shang; Xinning Tian; Hui Li (International Journal of Distributed Sensor Networks)
The load balancing technology is widely used in current enterprise network to provide high quality and reliable service. Conventional load balancing technology is often achieved by specific hardware that is usually very expensive and lacks sufficient flexibility. Meanwhile, it is easy to become a single point of failure and would be restricted in virtualization environments. Thus, we propose a load balancing algorithm based on server running state, which can calculate comprehensive loading according to the CPU utilization, memory utilization, and network traffic of the servers. Furthermore, a load balancing solution based on software defined networks (SDN) technology is applied in this paper, and it is designed and implemented in OpenFlow network. We combine network management and server state monitor in this scheme, in which the OpenFlow switches forward the request to the least comprehensive loading server by modifying the packet.